Real-life studies of biologics used in asthma patients: key differences and similarities to trials. (2nd September 2019) - Heffler, Enrico; Paoletti, Giovanni; Giorgis, Veronica; Puggioni, Francesca; Racca, Francesca; Del Giacco, Stefano; Bagnasco, Diego; Caruso, Cristiano; Brussino, Luisa; Rolla, Giovanni; Canonica, Giorgio Walter
ABSTRACT: Introduction : The precision medicine approach that is now mandatory for severe asthma management includes the use of novel biologic agents blocking specific immunological mechanisms that are responsible for disease phenotypes and endotypes: monoclonal antibodies blocking IgE, IL-5 and IL-4/IL-13 immunological pathways are so far available. Areas covered : Clinical trials involving a large number of patients proved their efficacy in reducing asthma exacerbations, improving lung function and quality of life, and reducing the need for systemic corticosteroid treatment. Since biologics have been available for routine use, a series of real-life experiences on severe asthmatics treated with them have been published: these studies confirmed the beneficial effects in a real-world setting (effectiveness) of these drugs and showed novel aspects that were not covered by clinical trials, such as their effect on particular subgroup of patients, unexpected adverse events, and potential novel indications. Expert opinion : Both clinical trials and real-life experiences are needed to establish robust data on biologic agents for severe asthma, with real-life studies giving more broader insights on different aspects related to the biologics themselves and to the disease.